A história da escola do hospital do pênfigo: da marginalidade ao reconhecimento publico em Uberaba/Mg (1959-1985) - Ribeiro, Ione (2019)
This is a research located in the field of History and Historiography of Education, inserted in the subarea of History of School Institutions, whose object of investigation is the Hospital do Pênfigo School, created in Uberaba / MG in 1959 in the hospital space called Hospital do Pênfigo Foliáceo, which remained in operation until 1985, the year in which it is legally recognized by Organs municipal bodies. The study was dedicated to analyzing the creation and organization of the school and its role with students and the surrounding community in structural, philosophical and political aspects, from 1959 to 1985. For this purpose, some questions were raised in order to conduct the study . What is the context for the creation of the Hospital do Pênfigo school and its social significance, considering the national, state and local historical context of organizing school education in general? How did the organization of school education take place within the institution, its specificities and characteristics? What is the profile and role of students, teachers and principals in the organization of educational practices? What is the meaning and significance of the school in the lives of the subjects involved in the process? The reasoning was based on the main theoretical and methodological references of historiographical research in the field of School Institutions, under the guidance of studies in this field. Documentary resources were fundamental, joining bibliographic sources, iconographic documents, legal framework for the regulation of education in all levels of government, and the methodological importance for collecting and analyzing data was also based on documents constructed from oral testimonies, which were collected through interviews with former coordinators and collaborators, former teachers and former students. In this methodological proposal, the dialectic between the local context and the state and national dimensions was established to understand how the legal determinations and the discourses present on the history of education and schooling reverberate in the local context. The study showed that the organization of the School of Hospital do Pênfigo reflects the model of education built in the country throughout the 20th century, revealing the difficulties encountered in school education as a “right for all”, further demonstrating the limits imposed by legislation regarding the (dis) commitment of the State in the “mandatory” education for the population, reinforcing the marginalization of a large part of society when it comes to access to school education. The reality experienced by the community served in the hospital institution when it was unable to insert its demand in regular school education was supported by an exclusive determination dictated by the national, regional and local education regulatory legislation which determined that those affected by serious and / or contagious disease and in poverty they were released from enrolling in the school unit. In view of this impasse, the creation of an educational space by the Hospital do Pênfigo became inevitable. Thus, the results confirmed the initial thesis that the School of Hospital do Pênfigo, although socially marginalized in its genesis as an improvisation school, but socially necessary, assumes the function of guaranteeing the schooling of a group, whose legislation excluded the mandatory imperative and the recognition of its meaning in the school life of the population. Despite the whole process of marginalization experienced by the patients and the very condition of the school, their teachers and their managers, especially the work of founder Dona Aparecida, managed to overcome the difficulties until their recognition as a public school, allowing the school insertion of a significant number of students. internal students of the institution as well as the existing demand in the surrounding community, changing the life trajectory of many of them. It is concluded that the Hospital do Pênfigo School had an expressive performance in the field of education in the city of Uberaba. However, her unique condition placed her in a dualistic position, by offering school education in circumstances different from the others, it was built in a format in which the prisoners in that space kept a distance from social life, also becoming a space of segregation reinforcing for some, the stigma of social marginalization. The public bodies responsible for expanding education for all in the municipality, exempted themselves from this support to the Hospital do Pênfigo School for decades, on the contrary, they started to use this school as an alternative to supply the needs of school places, often making it a space of institutionalizing poverty.